The Role of Connotation in differentiating Urdu Synonyms: A Linguistic Analysis - Hussain, Khadija Ghulam (Pakistan Languages and Humanities Review, 2025)
The study investigates the connotative meanings—positive, negative, and neutral—of Urdu synonymous with a specific focus on the influence of media on speakers residing in District Gujrat, Punjab. It delimits its scope to the Urdu vocabulary used in everyday communication. Languages evolve dynamically, and Urdu is no exception to this rule. The contextual use of words, politeness strategies, and emotive associations shape connotations, while the media further amplifies these shifts. Understanding how synonyms are emotionally interpreted helps reveal the interplay between language, culture, and media. A mixed-methods approach was employed, combining quantitative data from questionnaires with qualitative insights from interviews. The findings reveal that participants grade synonymous words differently, depending on their media exposure. Media portrayal often redefines neutral words to evoke positive or negative associations. Participants’ emotional interpretations highlight a significant role of television, social media, and print media in shaping connotative meanings. These variations demonstrate the inseparable link between media discourse and linguistic perception. Future studies should explore cross-district comparisons to broaden the scope of the results. Media literacy programs are recommended to sensitize audiences to linguistic shifts caused by mediated communication.